(untitled) (Quaestiones Disputatae: temas en debate, 2016)
This article is a presentation of Enrique Dussel’s thought from the perspective of the concept of (ad)journment as conceived by A. Leal and M. Villegas in an a yet to be published paper. This concept refers the action by which a given discourse is placed in a position which can be considered marginal when compared to a central or hegemonic one. Thus, we looked into early works of the Latin American philosopher for a categorical framework that would go beyond the one that originated in ancient Greece, this being the framework that has determined the direction of Western thought ever since. In this paper, the way in which Dussel has applied this categorical framework is examined, in order to think from both a philosophical as well as a political standpoint in a Latin American context; ultimately, this paper examines how this results in, precisely, an (ad)journment of Latin American thought in various intellectual fields of in Latin America.